Rotation at the crack tip under uniform heat flow in an infinite medium - Bhattacharya A. (My University, 2025)
A complex analysis of rigid body rotation is presented. The crack-tip rotation for a line crack subjected to steady uniform heat flow is obtained in terms of thermal stress intensity factor in shear mode of the crack, the material and thermal parameters and coordinates of points close to the crack tip. The shear strip configuration is analysed on the basis of rotation and displacement at the end of the shear strip. © 1996 Kluwer Academic Publishers.